ByzRev 06.2024.009: Nektarios Zarras, Ideology and Patronage in Byzantium.: Dedicatory Inscriptions and Patron Images from Middle-Byzantine Macedonia and Thrace (Βυζάντιος. Studies in Byzantine History and Civilization 21). Turnhout: Brepols 2023. - Parpulov, Georgi (The Byzantine Review, 2024)
Nektarios Zarras, Ideology and Patronage in Byzantium. Dedicatory Inscriptions and Patron Images from Middle-Byzantine Macedonia and Thrace (Βυζάντιος. Studies in Byzantine History and Civilization 21). Turnhout: Brepols 2023. 176 pp. 44 figs. – ISBN 978-2-503-60532-6